Stereotip Gender dan Dominasi Kapitalis dalam Iklan Televisi suatu Analisis Wacana Kritis Terhadap Iklan Televisi Citra Korporasi Gudang Garam di Bulan Ramadhan - Bhernadetta Pravita Wahyuningtyas; Endang Setiowati (Bina Nusantara University, 2013)
Advertising has many purposes including the formation of consciousness, creating the image of the product or brand, forming positive associations and encouraging consumer behavior. Basically, the purpose of advertising is to achieve economic hegemony of the producers of goods or service advertised. Ads are increasingly being used for the benefit of the capitalists. Corporate advertising researchers usually discuss the effects of advertising on the form of company image only. But this research is not going to reveal about the image of a company that advertised, but about the creator ideology behind the creation of a corporate Advertising. The corporate Ads examined in this study is a series of Gudang Garam corporate advertisement which consists of two ads that aired on television every Ramadan. The research method used is French critical discourse analysis and analytical method of Sara Mill. This study uses substantive theoretical framework such as hegemony, ideology, patriarchy, and Marxist feminism and the discourse analysis theory from Michael Foucault and semiotic theory of Roland Barthes. The results of this study showed that the ideology of the ad creator which is very patriarchal makes the text of the Gudang Garam corporate ads aired on all television stations every Ramadan, was laden with the existence of gender stereotypes.